Pollen Spectra from the Double Passage-Grave, Klekkendehøj, on Møn: Evidence of Swidden Cultivation in the Neolithic of Denmark - Th., Svend (Journal of Danish Archaeology, 1988)
Pollen Spectra from the Double Passage-Grave, Klekkendehøj, on Møn: Evidence of Swidden Cultivation in the Neolithic of Denmark